Use of foreign experience in the process of professional training of life safety teachers - Tairov Sherzod Mirzadjanivych (Zien Journals, 2022)
The article shows the experience of teaching schoolchildren and university students in the field of life safety in Israel and Spain and its use in the educational process of training life safety teachers at a pedagogical university.
Keywords: Life Safety; Teaching; Safety Teachers; Education